How to organize digital innovation in Icelandair Group? - Liv Vestergaard 1990- (2017)
Icelandair Group, an Icelandic conglomerate operating in the tourism and transportation sectors, faces challenging times due to competitive pressures from the increased tourism in Iceland. The corporation intends to strengthen its competitive situation through digital innovation. This study takes a knowledge-based approach and investigates how Icelandair Group can take advantage of social capital and knowledge transfer processes between subsidiaries when establishing a digital innovation unit. The purpose of this research was two-fold; First, to test a model of social capital and value creation by Tsai and Ghoshal (1998) in a new organizational context, a national conglomerate; Second, to recommend Icelandair Group how to structure the new digital unit. The research applied a case study design incorporating a questionnaire for data collection. Data were collected from 51 managers within Icelandair Group and analyzed through social network analysis and structural equation modeling. The study did not find support for the model that social capital increases value creation. The study found a significant relationship between social interaction ties and trust on inter-unit knowledge transfer. The study did not confirm that organizational knowledge transfer leads to innovation. The study recommends that Icelandair Group establishes an autonomous digital unit with a combination of permanent and rotating staff. This will enable the corporation to strengthen inter-unit social capital and knowledge transfer relationships for greater competitive advantage.